Factors Affecting Elderly Activeness In Participating In Posyandu: A Systematic Review - Dita Arditya Kusumadewi (Journals of Ners Community, 2023)
Posyandu for the elderly is an integrated service post for the elderly, including physical and mental-emotional health checks that are recorded and monitored with the Card Towards Health (KMS). The purpose of this systematic review is to describe and analyze the relationship between knowledge, attitudes, family support and infrastructure with the activities of the elderly who visit the Elderly Posyandu. The design uses a systematic review of narrative. The method used is the prism method which is carried out systematically. There were 11 articles that were analyzed in this systematic review process. It was found that the factors that influence the activity of the elderly in participating in the posyandu are knowledge, attitudes and behavior, subjective norms, family support, facilities and infrastructure, the affordability of posyandu from home, and physical complaints. Some of these factors are needed to increase the success of the posyandu for the elderly.